Pemikiran Ekonomi Islam Kontemporer (Muhammad Baqir Als Sadr, Ibrahim Umar Vadillo, dan M. Umer Chapra) - Aisyah, Aisyah; Hayati, Fitri; Saragih, Lutfiah Irwani; Ananda, Nabila Tri; Syofianda, M. Uki (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study discusses contemporary Islamic economic thought with a focus on the contributions of Muhammad Baqir al-Sadr, Ibrahim Umar Vadillo, and M. Umer Chapra. This study uses a descriptive qualitative method through a library study of various literature and documents related to Islamic economics. The results of the study indicate that al-Sadr emphasizes social justice and the role of the state in the distribution of wealth, Vadillo offers a dinar and dirham-based monetary system for economic stability, and Chapra emphasizes social welfare through zakat, prohibition of usury, and strengthening of Islamic financial institutions. All three agree that Islamic economics must integrate moral values, ethics, and sharia principles in resource management and wealth distribution. Thus, contemporary Islamic economics offers practical and relevant solutions to the challenges of the modern economy by emphasizing aspects of justice, welfare, and sustainability.